2003
DOI: 10.1002/per.467
|View full text |Cite
|
Sign up to set email alerts
|

The additive and interactive effects of parenting and children's personality on externalizing behaviour

Abstract: Parenting practices have been previously linked to childhood externalizing behaviour. However, little attention has been given to the potential effect of individual personality differences among children on this relation. The current study assesses the additive effects of children's personality characteristics and explores the moderating effects of children's personality on relations between parenting practices and childhood externalizing behaviour using a proportional stratified sample of 599 nonclinical elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
158
3
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(192 citation statements)
references
References 61 publications
22
158
3
9
Order By: Relevance
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
See 4 more Smart Citations
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
“…However, previous research has mainly focused on the associations between behavioral problems and measures of adaptive personality traits. For example, research in representative community samples has identified consistent relationships between low Conscientiousness, low Agreeableness, high Extraversion and to a lesser extent high Neuroticism (Prinzie et al, 2003;Prinzie, Van der Sluis, De Haan, & Deković , 2010;Tackett, 2006;Van Leeuwen, Mervielde, Braet, & Bosmans, 2004) and behavioral problems. Given the importance of personality in the forthcoming DSM-V (Widiger, 2011;Widiger & Mullins-Sweatt, 2009) and the fact that maladaptive personality traits have not yet been studied in children with MID, the third aim of this study was to investigate the association of behavioral problems with maladaptive personality traits.…”
Section: Maladaptive Personality Traitsmentioning
confidence: 99%
See 3 more Smart Citations